Study Protocol for the Preschooler Regulation of Emotional Stress (PRES) Procedure - Provenzi, Livio; Cassiano, Rafaela G. M.; Scotto di Minico, Giunia; Linhares, Maria B. M.; Montirosso, Rosario (Frontiers in Psychology, 2017)
Background: Emotional stress regulation (ESR) rapidly develops during the first months of age and includes different behavioral strategies which largely contribute to children’s behavioral and emotional adjustment later in life. The assessment of ESR during the first years of life is critical to identify preschool children who are at developmental risk. Although ESR is generally included in larger temperament batteries [e.g., the Laboratory Temperament Assessment Battery (Lab-TAB)], there is no standardized observational procedure to specifically assess and measure ESR in preschool aged children. Aim: Here, we describe the development of an observational procedure to assess ESR in preschool aged children [i.e., the Preschooler Regulation of Emotional Stress (PRES) Procedure] and the related coding system. Methods: Four Lab-TAB emotional stress episodes (i.e., the Stranger, the Perfect Circle, the Missing Sticker, and the Transparent Box) have been selected. Independent coders developed a list of ESR codes resulting in two general indexes (i.e., active engagement and stress level) and five specific indexes (i.e., anger, control, fear, inhibition, sadness). Finally, specific actions have been planned to assess the validity and the coding system reliability of PRES procedure. Ethics and Dissemination: The study has been approved by the Ethical Committee of the Scientific Institute IRCCS Eugenio Medea, Bosisio Parini (Italy). The PRES validation and reliability assessment as well as its use with healthy and at-risk populations of preschool children will be object of future scientific publications and international conference presentations.